2018
DOI: 10.4103/jovr.jovr_193_17
|View full text |Cite
|
Sign up to set email alerts
|

Association of FOXE3-p.Ala170Ala and PITX3-p.Ile95Ile polymorphisms with congenital cataract and microphthalmia

Abstract: Purpose:To investigate the association of FOXE3-p.Ala170Ala (rs34082359) and PITX3-p.Ile95Ile (rs2281983) polymorphisms with congenital cataract and microphthalmia in a western Indian population.Methods:FOXE3-p.Ala170Ala (c.510C>T) and PITX3-p.Ile95Ile (c.285C>T) polymorphisms were genotyped in 561 subjects consisting of 242 cases with congenital cataract, 52 with microphthalmia, and 267 controls using polymerase chain reaction-restriction fragment length polymorphism. Approximately 10% of samples were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Even if the intronic SNP does not have a functional consequence, it may exist in linkage disequilibrium with other functional SNPs and thereby help recognize the disease loci. Considering the potential association of SNPs with congenital cataract and the dearth of information on genetic association studies using intronic SNPs,[ 38 39 ] the present study was performed to understand the distribution of intronic SNPs rs3788059 ( CRYAA ), rs2070894 ( CRYAB ), rs2071861 ( CRYBA4 ), rs5752083 ( CRYBB2 ), and rs5996863 ( CRYBB2 ) in congenital cataracts and normal healthy controls. Although association studies using these markers have never been reported in congenital cataracts, studies on rs2070894 concerning colorectal and oral cancer[ 40 41 ] and rs2071861 concerning high myopia[ 42 43 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the intronic SNP does not have a functional consequence, it may exist in linkage disequilibrium with other functional SNPs and thereby help recognize the disease loci. Considering the potential association of SNPs with congenital cataract and the dearth of information on genetic association studies using intronic SNPs,[ 38 39 ] the present study was performed to understand the distribution of intronic SNPs rs3788059 ( CRYAA ), rs2070894 ( CRYAB ), rs2071861 ( CRYBA4 ), rs5752083 ( CRYBB2 ), and rs5996863 ( CRYBB2 ) in congenital cataracts and normal healthy controls. Although association studies using these markers have never been reported in congenital cataracts, studies on rs2070894 concerning colorectal and oral cancer[ 40 41 ] and rs2071861 concerning high myopia[ 42 43 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%